Community‐based adaptation research in the Canadian Arctic. (25th November 2015) - Ford, James D.; Stephenson, Ellie; Cunsolo Willox, Ashlee; Edge, Victoria; Farahbakhsh, Khosrow; Furgal, Christopher; Harper, Sherilee; Chatwood, Susan; Mauro, Ian; Pearce, Tristan; Austin, Stephanie; Bunce, Anna; et al.
Abstract : Community‐based adaptation (CBA) has emerged over the last decade as an approach to empowering communities to plan for and cope with the impacts of climate change. While such approaches have been widely advocated, few have critically examined the tensions and challenges that CBA brings. Responding to this gap, this article critically examines the use of CBA approaches with Inuit communities in Canada. We suggest that CBA holds significant promise to make adaptation research more democratic and responsive to local needs, providing a basis for developing locally appropriate adaptations based on local/indigenous and Western knowledge. Yet, we argue that CBA is not a panacea, and its common portrayal as such obscures its limitations, nuances, and challenges. Indeed, if uncritically adopted, CBA can potentially lead to maladaptation, may be inappropriate in some instances, can legitimize outside intervention and control, and may further marginalize communities. We identify responsibilities for researchers engaging in CBA work to manage these challenges, emphasizing the centrality of how knowledge is generated, the need for project flexibility and openness to change, and the importance of ensuring partnerships between researchers and communities are transparent. Researchers also need to be realistic about what CBA can achieve, and should not assume that research has a positive role to play in community adaptation just because it utilizes participatory approaches. WIREs Clim Change 2016, 7:175–191. doi: 10.1002/wcc.376 This article is categorized under: Vulnerability and Adaptation to Climate Change > Learning from Cases and Analogies